Assessing Product Satisfaction Performance using 6-Sigma Methodology and S/N Ratio Approach - the case of PDA - Tao, Chia-Jen; Chen, Shui-Chuan; Hsieh, Chin-Tsung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
With the advent of the Internet, personal digital assistants (PDAs), which were originally meant for management of personal information, are now equipped with the features of network connection and wireless communication. No longer restricted by time and space, PDAs can access information anytime and anywhere, thus resembling a palm-top computer. Nevertheless, the upsurge of Information Appliances (IAs) has bred over-optimism on the development of PDAs. In terms of importance, PDAs are inferior to mobile phones; while in terms of functions, they are less versatile than notebook PCs. Such perspective, however, has neglected the uniqueness of PDAs. In view of the sluggish sale of PDAs, this study aims to explore how production satisfaction, brand name, and service convenience affect the desire to purchase PDAs, which can serve as useful references for planning IA promotion strategies. By utilizing the DMAIC methodology of 6-sigma, a comprehensive assessment and improvement model is constructed. This model enables enterprises to quickly and effectively measure, analyze, improve and control their service quality, which would in turn promote the overall satisfaction of customers, thus creating high value-added quality competitiveness and enhancing the profitability of enterprises.